2017
DOI: 10.1016/j.oregeorev.2017.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of sulfate and carbonaceous rocks: Experimental study, thermodynamic modeling and application to the Noril’sk-Talnakh region (Russia)

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. sulfate and organic matter-rich sedimentary rocks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…This assimilation enriches the melt in S and to a lesser extent in CaO, while decreases its silica content (Figs. SI6a-b), and strongly oxidizes the magma (Iacono-Marziano et al 2017). Being this a local process that depends on the physical path followed by each magma upon its ascent, and also on its temperature and ascent rate, sulfate assimilation could therefore account for (i) the changes in the redox conditions (and the resulting different timings and amounts of spinel crystallization) observed between the different eruptions (section 4.1.4, Fig.…”
Section: Additional Processes Contributing To Magmas Heterogeneitymentioning
confidence: 99%
“…This assimilation enriches the melt in S and to a lesser extent in CaO, while decreases its silica content (Figs. SI6a-b), and strongly oxidizes the magma (Iacono-Marziano et al 2017). Being this a local process that depends on the physical path followed by each magma upon its ascent, and also on its temperature and ascent rate, sulfate assimilation could therefore account for (i) the changes in the redox conditions (and the resulting different timings and amounts of spinel crystallization) observed between the different eruptions (section 4.1.4, Fig.…”
Section: Additional Processes Contributing To Magmas Heterogeneitymentioning
confidence: 99%
“…FiGure 5. Parts per million of S6+ determined from Raman calibration as a function of parts per million of S determined from EPMA measurements from Gennaro (2017) and Iacono-Marziano et al (2017) for basalt melt inclusions collected from Etna lava flows and basalt glasses synthesized at high pressure (80-200 MPa) and fO2 conditions below QFM+1.5 (see Appendix1 Table 1). Raman measurements are in favor of an unaccounted amount of S attributed to S2-species.…”
Section: Implications: Determining Redox Conditions In Silicate Melt mentioning
confidence: 99%
“…Crustal assimilation and contamination and fractional crystallization typically occur simultaneously during the evolution and emplacement of magma [53], and the crustal assimilation and contamination, which often occur during the formation of a large-scale Ni-Cu deposit, are considered to be some of the key factors in the formation of a magmatic Ni-Cu sulfur deposit (Voisey's Bay [4], Jinchuan [5], Noril'sk [9], and Xiarihamu [54]). First of all, the presence of many xenoliths in the Niubiziliang complex indicates that crustal contamination inevitably occurs during the emplacement of magma.…”
Section: Crustal Assimilation and Contaminationmentioning
confidence: 99%
“…Many investigations have indicated that sulfide liquation led to a sharp loss of Ni content in magma under sulfur saturation, and thus the olivine also showed a loss of Ni [3,9]. In other words, the Ni content of olivine was significantly controlled by sulfide liquation, and the Ni deficit in olivine was determined by the volume ratio of olivine to sulfide, in magma.…”
Section: Sulfur Saturation Mechanismmentioning
confidence: 99%
See 1 more Smart Citation